Genetics of Severe Myoclonic Epilepsy of Infancy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The role of SCN1A gene mutations in the etiology of severe myoclonic epilepsy of infancy (SMEI) was investigated in 93 patients followed at the Hopital Saint Vincent de Paul, Paris, and other centers in France and Italy.